Penggunaan Alat Bukti Keterangan Saksi A Charge Dalam Pembuktian Tindak Pidana Penipuan Tenaga Kerja - Ignasius Ninorey (Verstek, 2017)
The purpose of research are, first whether the use of evidence of a charge witness description in criminal fraud towards manpower in accordance with the provisions of Criminal Procedure Code, second whether of a charge witness description in criminal fraud investigation towards manpower be considered by the judge.    This is normative research with case approach. Data collection technique include study of literature, use of deductive logic of this research, and a qualitative analysis.    Research is related to fraud cases labor done Icha to Prihandoko where Icha claimed to have acquaintance in disnaker solo named Mrs. Diah and could he is sending prihandoko as migrant workers abroad. Icha asking for money Prihandoko IDR.6.730.000,- ( six million seven hundred thirty thousand rupiah) to the cost of a and management of the cost of migrant workers , but after waited a long time, Prihandoko not to be going abroad. When clarified to disnaker solo , it turns out that Mrs. Diah not at the sending migrant workers but administrative officer and recognize Icha. Because they felt deceived, then prihandoko reported Icha to the related authorities to go to court.     Results of research show that the use of evidence in a charge witness description in criminal fraud towards manpower has fulfilled the provisions of Criminal Procedure Code, hereinafter conformity of the judge's consideration of a charge witness description in criminal fraud investigation towards manpower that a charge witness description which submitted public prosecutor to reinforce its arguments highly considered by the judge and also affecting conviction the judge in drop down the verdict.     Keywords: A Charge Witness Description, Evidence and Criminal Fraud.